PENGARUH ENTREPRENEURIAL SELF-EFFICACY TERHADAP GREEN ENTREPRENEURIAL INTENTION YANG DIMEDIASI OLEH PENDIDIKAN KEWIRAUSAHAAN: Survei pada Mahasiswa Startup Fakultas Pendidikan Ekonomi dan Bisnis Universitas Pendidikan Indonesia. - LINDA MARYANI; Endang Supardi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Green entrepreneurial Intention as a form of individual attitude can be influenced by performance and the social environment can be influenced by self-efficacy, individuals involved in the business organization. In realizing this, it is necessary to conduct research to test empirically the Effect of Green Entrepreneurial Intention on Entrepreneurial Self-Efficacy mediated by Entrepreneurship Education. The main objective of this study was to examine the effect as measured subjectively by students. Not a few business people only care about profits, regardless of threats to environmental sustainability. This type of research is quantitative using survey methods. The sample collection technique in this study used the Proportional Allocation technique. The results of this study indicate that there is an influence of Entrepreneurial Self-Efficacy on Green Entrepreneurial Intention which is mediated by entrepreneurship education. This is based on hypothesis testing partial and simultaneous where each of these variables has an influence. Keywords: Entrepreneurial Self-Efficacy, Green Entrepreneurial Intention, Entrepreneurship education.